CONTROLLING WHAT IS WRITTEN: ARISTOCRATIC INTERFERENCE WITH BURGOS’S CLERK OFFICE IN THE LATE MIDDLE AGES. - Montero Málaga, Alicia Inés (Imago Temporis. Medium Aevum, 2025)
The aim of this article is to examine the head clerk’s office in the realengo (under royal jurisdiction) city of Burgos during the fifteenth century. I will analyse the professional path that gave access to this office, its functions and its duties, and I will also go over the holders of this position in the fifteenth century. I will examine the appropriation of this post by the lineage of the Fernández de Velasco, Counts of Haro, condestables of Castile, and Dukes of Frías, members of the high Castilian nobility. Special attention will be paid to the mechanisms used by the nobility to access this public office, as well as to the scope and meaning of their control over the head clerk’s office.